A new species of mecochirid lobster, Meyeria libanotica (Decapoda, Glypheoidea), from the Barremian (Early Cretaceous) of Lebanon - Charbonnier, Sylvain; Audo, Denis; Garassino, Alessandro; Simpson, Martin; Gèze, Raymond; Azar, Dany (Annales de Paléontologie, 2021)
International audience A large sample of mecochirid lobsters (Crustacea, Decapoda, Mecochiridae) has been recently collected from the early Barremian (Early Cretaceous) of Lebanon. The studied specimens are described as Meyeria libanotica sp. nov. The genus Meyeria M’Coy, 1849 is also revised and new combinations are proposed for two species: Meyeria bartholomaii (Jell, Woods, and Cook, 2017) comb. nov. (Aptian, Australia), and Meyeria rostrata (Collins and Rasmussen, 1992) comb. nov. (Campanian–Maastrichtian, Greenland). The stratigraphic range and the palaeogeographic distribution of Meyeria are consequently recognized to spread from the Oxfordian (Late Jurassic) to the Maastrichtian (Late Cretaceous) and from Australia to Greenland, passing by Europe, respectively. Un riche échantillon de langoustes mécochiridées (Crustacea, Decapoda, Mecochiridae) a été récemment récolté dans le Barrémien inférieur (Crétacé inférieur) du Liban. Les spécimens étudiés sont attribués à Meyeria libanotica sp. nov. Le genre Meyeria M’Coy, 1849 est aussi révisé et de nouvelles combinaisons sont proposées pour deux espèces: Meyeria bartholomaii (Jell, Woods, et Cook, 2017) comb. nov. (Aptien, Australie), et Meyeria rostrata (Collins et Rasmussen, 1992) comb. nov. (Campanien–Maastrichtien, Groenland). La répartition stratigraphique et la distribution paléogéographique de Meyeria s’étendent maintenant respectivement de l’Oxfordien (Jurassique supérieur) au Maastrichtien (Crétacé supérieur) et de l’Australie au Groenland en passant par l’Europe.